SHARIAH ISSUES IN INTANGIBLE ASSETS - Bouheraoua, Said; Mohamad, Shamsiah; Kasri, Noor Suhaida; Abdullah, Syahida (Jurnal Syariah, 2015)
Intangible assets are regarded as one of the most important asset classes for financial institutions, and their importance and consideration is rapidly increasing. There are existing, well established conventional standards on intangible assets (IA); however the Shariah standard on IA is discussed rather minimally. Thus, this paper attempts to discuss the vital issues related to intangible assets: recognition and measurement, financing and trading, and zakÄh, which represents a grey area for the Islamic finance industry. The research employs critical analysis. It aims to provide clarification on the concept of intangible assets from the point of view of the Shariah as well as an analysis of pertinent Shariah issues on IA. This research explores the following: (i) there is an issue of gharar in the identification and determination of IA due to non-existence of any physical substance and due to future benefit being a probabilistic matter; (ii) it is generally permissible to finance and trade IA and (iii) zakÄh is obligatory on IA if the intention is to trade them either at sale price if they are sold or at market price if they are owned by a trader.